Monte Carlo Simulation Modeling of a Regional Stroke Team's Use of Telemedicine. (31st December 2015) - Torabi, Elham; Froehle, Craig M.; Lindsell, Christopher J.; Moomaw, Charles J.; Kanter, Daniel; Kleindorfer, Dawn; Adeoye, Opeolu
Abstract: Objectives: The objective of this study was to evaluate operational policies that may improve the proportion of eligible stroke patients within a population who would receive intravenous recombinant tissue plasminogen activator (rt‐PA) and minimize time to treatment in eligible patients. Methods: In the context of a regional stroke team, the authors examined the effects of staff location and telemedicine deployment policies on the timeliness of thrombolytic treatment, and estimated the efficacy and cost‐effectiveness of six different policies. A process map comprising the steps from recognition of stroke symptoms to intravenous administration of rt‐PA was constructed using data from published literature combined with expert opinion. Six scenarios were investigated: telemedicine deployment (none, all, or outer‐ring hospitals only) and staff location (center of region or anywhere in region). Physician locations were randomly generated based on their zip codes of residence and work. The outcomes of interest were onset‐to‐treatment (OTT) time, door‐to‐needle (DTN) time, and the proportion of patients treated within 3 hours. A Monte Carlo simulation of the stroke team care‐delivery system was constructed based on a primary data set of 121 ischemic stroke patients who were potentially eligible for treatment with rt‐PA. Results: With the physician located randomly in the region, deploying telemedicine at all hospitals in the region (compared with partial or no telemedicine) would result in the highest rates of treatment within 3 hours (80% vs. 75% vs. 70%) and the shortest OTT (148 vs. 164 vs. 176 minutes) and DTN (45 vs. 61 vs. 73 minutes) times. However, locating the on‐call physician centrally coupled with partial telemedicine deployment (five of the 17 hospitals) would be most cost‐effective with comparable eligibility and treatment times. Conclusions: Given the potential societal benefits, continued efforts to deploy telemedicine appear warranted. Aligning the incentives between those who would have to fund the up‐front technology investments and those who will benefit over time from reduced ongoing health care expenses will be necessary to fully realize the benefits of telemedicine for stroke care.